Polyphenism – A Window Into Gene-Environment Interactions and Phenotypic Plasticity - Yang, Chih-Hsiang; Andrew Pospisilik, John (Frontiers in Genetics, 2019)
Phenotypic plasticity describes the capacity of a single genotype to exhibit a variety of phenotypes as well as the mechanisms that translate environmental variation into reproducible phenotypic modifications. Polyphenism describes the unique sub-type of phenotypic plasticity where the outputs are not continuous, but rather discrete and multi-stable, resulting in several distinct phenotypes on the same genetic background. Epigenetic regulation underpins the stable phenotypic divergences that exemplify polyphenism, and their evolutionary origin. Here, we briefly summarize the apparent ubiquity and diversity of polyphenisms across the animal kingdom. We will briefly review the best characterized models across taxa, and highlight consistent themes both in their epidemiology and what little we know about molecular mechanisms. Finally, we will highlight work that supports the possibility that humans may have a subtle polyphenism at the level of metabolism.